Embracing the Innovative Entrepreneurship Culture by Omani SMEs: The Primary Barriers - Alhattali, Khalid Suraid Salim; Omar, Rosmini; Alrumaidhi, Sulaiyam Aziz; Mohammadi, Parisa (Business Management and Strategy, 2023)
Many countries increasingly recognise innovative entrepreneurship as a key component that stimulates innovation, creates job opportunities, and improves long-term societal welfare. However, it faces numerous challenges in different countries, including the Sultanate of Oman, which may hinder its development or slow down its pace. Accordingly, this qualitative study aimed to identify the primary barriers preventing innovative entrepreneurship culture among Omani SMEs. The results introduced six primary barriers: Bureaucracy and inefficiency of government officers, COVID-19 pandemic, Negative mind-set and frustration with the market, Poor financial management, Financial burden, and No additional benefits or supports. The empirical findings of this study have both academic and practical contributions to the body of knowledge; they elaborate on the long-term performance of innovative entrepreneurship and economic growth in Oman.